2015
DOI: 10.1016/j.ejpal.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Undeutsch hypothesis and Criteria Based Content Analysis: A meta-analytic review

Abstract: A B S T R A C TThe credibility of a testimony is a crucial component of judicial decision-making. Checklists of testimony credibility criteria are extensively used by forensic psychologists to assess the credibility of a testimony, and in many countries they are admitted as valid scientific evidence in a court of law. These checklists are based on the Undeutsch hypothesis asserting that statements derived from the memory of real-life experiences differ significantly in content and quality from fabricated or fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0
21

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 36 publications
9
122
0
21
Order By: Relevance
“…As expected, participants primarily reported nonverbal cues-most notably gaze aversion and nervous behavior-as useful for detecting deception, replicating our previous study (Bogaard et al, 2016), as well as many others (e.g., Akehurst et al, 1996;Masip & Herrero, 2015;Strömwall et al, 2004;Strömwall & Granhag, 2003;Taylor & Hick, 2007;Vrij et al, 2006;Vrij & Semin, 1996). Although verbal signals were reported to a lesser extent, the cues that were reported (i.e., inconsistencies, details, and coherence) were largely supported by empirical research (Amado et al, 2015;Amado, Arce, Fariña, & Vilariño, 2016;Masip et al, 2005;Oberlader et al, 2016;Vrij, 2005).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected, participants primarily reported nonverbal cues-most notably gaze aversion and nervous behavior-as useful for detecting deception, replicating our previous study (Bogaard et al, 2016), as well as many others (e.g., Akehurst et al, 1996;Masip & Herrero, 2015;Strömwall et al, 2004;Strömwall & Granhag, 2003;Taylor & Hick, 2007;Vrij et al, 2006;Vrij & Semin, 1996). Although verbal signals were reported to a lesser extent, the cues that were reported (i.e., inconsistencies, details, and coherence) were largely supported by empirical research (Amado et al, 2015;Amado, Arce, Fariña, & Vilariño, 2016;Masip et al, 2005;Oberlader et al, 2016;Vrij, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…CBCA items were scored on the basis of Amado, Arce, and Fariña (2015), DePaulo et al (2003), and Vrij (Vrij, 2005(Vrij, , 2008b. A CBCA item was scored as diagnostic if the item was significantly more present in truthful statements compared with fabricated statements in more than 65% of the studies included in the meta-analyses of Vrij (2005Vrij ( , 2008b and/or showed an effect size of at least d = 0.50 in Amado et al (2015) and/or a significant difference in DePaulo et al (2003). In total, 10 cues were evaluated as diagnostic of deceit, while evidence for seven items was mixed and hence was evaluated as nondiagnostic.…”
Section: Relationship With Extant Literaturementioning
confidence: 99%
“…Complications are more likely to occur in truthful statements than in deceptive statements (Amado, Arce, & Fariña, 2015;Vrij, Fisher, et al, 2017;. Making up complications requires imagination, and liars may not have adequate imagination to make up facts (Vrij, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The statement "I can't remember" itself is not a self-handicapping strategy, it is called admitting lack of memory and part of the criteriabased content analysis tool (Amado et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Psicología y Derecho aúnan posiciones teóricas, metodológicas y aplicadas para entender los factores propios de las personas, a nivel social, psicológico, conductual, relacional, de salud, entre otros, que afectan o pueden afectar al comportamiento legal de todos los actores que intervienen en el proceso de forma directa como jurados, jueces, peritos, testigos, víctimas, agresores, investigadores, cuerpos de seguridad, o de forma indirecta como grupos de riesgo o la población en general en los estudios relacionados con prevalencia de conductas delictivas, la prevención del riesgo o la influencia de la sociedad, del barrio o de la familia en determinados comportamientos que pueden conducir a un proceso legal (González-Sala, Osca-Lluch, Tortosa y Peñaranda, 2017). Por este motivo, la psicología jurídica tiene un papel fundamental en la toma de decisiones judiciales (Amado, Arce y Fariña, 2015;Amado, Arce, Fariña y Vilariño, 2016;Arce, Fariña y Fraga, 2000) y en la resolución de temas tan lamentables y frecuentes como la violencia doméstica y malos tratos tanto en adultos (Arce, Fariña y Vilariño, 2015; Cala, Trigo y Saavedra, 2016; Contreras y Cano, 2016) como en adolescentes (Álvarez-García, Barreiro-Collazo, Núñez y Dobarro, 2016).…”
Section: Introductionunclassified